The effectiveness of using the Spelling Bee method to improve Arabic vocabulary comprehension among Junior High School Students of Dar El-Hikmah Pekanbaru/ Fa’ãliyatu Istikhdãmi TarÎqah Spelling Be Litarqiyati Isti’ãb al-Mufradãt al-Arabiyah lada Thullãbi fi al-Madrasah al-Mutawassithah bi Ma’hadi Dãr al-Hikmah Pekanbaru - Prabangestha, Prabangestha; Kasmiati, Kasmiati; Masbukin, Masbukin (Al-Manar, 2023)
ملخّصيستخدم هذا البحث مقاربة كميا مع تصميم البحث التجربي، يتكون من متغيرين وهما طريقة "Spelling Bee (X) واستيعاب المفردات (Y). يهدف البحث لمعرفة فعالية استخدام طريقة "Spelling Bee" لترقية استيعاب المفردات العربية لدى طلاب الصف الثامن في المدرسة المتوسطة بمعهد دار الحكمة بكنبارو. وسؤال البحث فيه هل استخدام طريقة "Spelling Bee" فعال لترقية استيعاب المفردات لدى طلاب الصف الثامن في المدرسة المتوسطة بمعهد دار الحكمة بكنبارو. أداتان لجمع البيانات هي اختبار و ملاحظة. وكان الاختبار الذي قامت به الباحثة هو إجراء الصلاحية والموثوقية على أسئلة الاختبار القبلي. من بين 30 سؤال التي تم اختبار صلاحيتها، تمت الحصول على 25 سؤالا صالحة وكانت 5 سؤال غير صالحة مع قيمة موثوقية 0.89 (عالي).استنادا من نتيجة الاختبار القبلى و الاختبار البعدي في الفصل التجريبي تحصل الباحثة على قيمة 10 و في الفصل الضبطي تحصل الباحثة على قيمة 6,4. وبناء على تحليل البياناتبرموز t-test عرف بأن قيمة حساب t = 5 وهي أعلى من قيمة جدول t في مستوى دلالة ٪1= 2,70 ومستوى دلالة ٪5=2,02. فالفرضية المبدئية  (H0)مردودة والفرضية البديلة  (Ha)مقبولة، وذلك بمعنى أن هناك أثرا هاما لاستخدام طريقة "Spelling Bee"في استيعاب المفردات. وكذلك في جدول ملاحظة "Spelling Bee" نيل ٪96 بمعنى "جيد جدا" لإنه يقع في درجة ٪90- ٪100. باستخدام هذه البيانات، تم الحاصل من هذا البحث أن استخدام طريقة "Spelling Bee" فعال لترقية استيعاب المفردات لدى طلاب الصف الثامن في المدرسة المتوسطة بمعهد دار الحكمة بكنبارو.  AbstractThis research uses a quantitative approach with an experimental research desaign comprising two variables— Spelling Bee Method (X) and vocabulary mastery (Y).  This research aimed at knowing the effectiveness Spelling Bee Method in Increasing Student Vocabulary Mastery of Grade VIII of MTs Dar El Hikmah Pekanbaru.  The formulation of the problem in this research was was spelling bee method effective in increasing student vocabulary mastery of Grade VIII of MTs Darel Hikmah Pekanbaru? Test and Observation were the instruments of collecting data. The test that the reseacrher did was to do the validity and realibity on the pre-test questions, of the 30 questions that were tested for validity, 25 items were obtained that were valid and 5 items were invalid with a realibility value of 0,89 (high). Based on the result of the pre test and post test in the exerimental class, the reseacher got a value of 10  and in the control class, the reseacher got a value of  6,4. Based on data analysis using the t-test formula, it was obtained that the score of tobserved 5.70 was higher than ttable 2.02 at 1% significant level and 1.68 at 5% significant level.  So, nol hypotheses (H0) was rejected and alternative hypotheses (Ha) was accepted.  It meant that there was a significant increase of vocabulary mastery of students taught by using spelling bee method. As well as in the observation table, the spelling bee  method got a value of  96% with the meaning very good because it is located at a significant level 90% -100%. With these data, the spelling bee  method was declared effective to improve the vocabulary mastery of grade VIII of MTs Dar El Hikmah Pekanbaru